Authentic Sources of Research Development of Rural Pre-School Institutions in Ukraine during the Period from 1945 to 1991 - Melenets’, Lyudmyla (Pedagogical Discourse, 2013)
This publication analyzes the current state of the authentic sources of preschool rural Ukraine in the historical and pedagogical space of 1945-1991 years. Definitely chronology of regulatory policy legal support development of rural pre-school between 1947 and 1959. The role of the professional edition as an important record of events and achievements in the field of early childhood education is emphasized. We prove that without knowledge of the facts set forth periodicals, events, and scientific generalizations cannot be comprehended character specific historical period. The problem of pre-schools in rural areas of Ukraine is deeply investigated.